Genetic variability of corynespora cassiicola infecting hevea brasiliensis isolated from the traditional rubber growing areas in India - Saha T; Jacob C K; Joseph A; Kothandaraman R; Kumar K A; Nazeer M A; Sreena A S (Indian Journal of Natural Rubber Research, 2000)
Molecular characteristics of 20 isolates of Corynespora cassiicola from 16 different locations of two rubber growing states of southern India viz., Kerala and Karnataka, were investigated using random amplified polymorphic DNA (RAPD) markers. RAPD analysis clearly indicated the existence of at least seven different genotypes of C. cassiicola. Considerable genetic variations were detected among the Kerala isolates and three of them, KL01/97, KL04/98 and KL06/97 showed completely different RAPD profiles from others with each of the primers tested. Putative virulence specific RAPD profile of Corynespora was identified among the isolates where the disease became epidemic in Karnataka. Genetic relationships were established among the Corynespora isolates.
Keywords: Corynespora cassiicola; Genetic diversity; Hevea brasiliensis; Leaf disease; RAPD